Primary cilium and autophagy: The avengers of cell-size regulation. Issue 11 (1st November 2016) - Orhon, Idil; Dupont, Nicolas; Codogno, Patrice
ABSTRACT: The maintenance of cellular homeostasis in response to extracellular stresses by autophagy is vital for the health of various tissues. Extracellular stimuli may include nutrient starvation, endoplasmic reticulum stress, hypoxia, cytotoxic agents, or mechanical stress. The primary cilium (PC) is a microtubule-based sensory organelle that regulates the integration of various extracellular stimuli. The interconnection between macroautophagy/autophagy and the PC is beginning to be illuminated. In this punctum, we discuss our recent study of PC-dependent autophagy in response to fluid flow in kidney epithelial cells. Urinary flow in kidney tubules creates a shear stress that regulates epithelial cell volume. PC-mediated autophagy is necessary for the regulation of cell size. The signal from the PC is transduced by the activation of STK11/LKB1 and by MTOR inhibition. Our results clarify the physiological role of PC-dependent autophagy in the kidney and suggest that autophagy manipulation may provide a route to the treatment of ciliopathies.